A Review on Significance of Ksheer Yavagu with Ghirta in Garbhini Paricharya - Muskan; Rachna; Rani, Seema (International Research Journal of Ayurveda & Yoga, 2025)
Pregnancy embodies the incredible process of creating life and exhibiting the body’s ability to nurture and grow a new being. Garbhini paricharya (care of pregnant women) is well prescribes in Ayurveda. Garbhini Paricharya is a detailed month-wise traditional regimen that followed by Pregnant women. A systemic month-wise dietary and lifestyle regimen during different stages of pregnancy due to that fact it directly provides adequate nutrition to the pregnant women and growing fetus. In Garbhini Paricharya Acharya Charaka mentioned various Dravya as Pathya apathaya but gives more importance to ghrita, Ksheer, and ksheersidha Yavagu which plays a key role in promoting both maternal and fetal health. The present article explores about intervention of Ksheer, Yavagu mixed with Ghritain pregnancy and its clinical significance.